2010
DOI: 10.1007/s10571-010-9636-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that l-Carnitine and Selenium Supplementation Reduces Oxidative Stress in Phenylketonuric Patients

Abstract: It is well established that the involvement of reactive species in the pathophysiology of several neurological diseases, including phenylketonuria (PKU), a metabolic genetic disorder biochemically characterized by elevated levels of phenylalanine (Phe). In previous studies, we verified that PKU patients (treated with a protein-restricted diet supplemented with a special formula not containing L-carnitine and selenium) presented high lipid and protein oxidative damage as well as a reduction of antioxidants when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 47 publications
3
34
0
4
Order By: Relevance
“…The reported mechanisms for the L-carnitine antiperoxidative role include inhibition of xanthine oxidase activity, scavenger action of free radicals, and chelation of the iron required for the generation of hydroxyl radicals [45,46] or by facilitating the fatty acids transport, thereby lowering the availability of lipids for peroxidation [47]. Reinforcing the hypothesis that L-carnitine could prevent lipid peroxidation in HMGA, this same protective effect was observed in other inborn errors of metabolism, such as in phenylketonuria [48], in maple syrup urine disease [24,31], and in disorders of propionate metabolism [28,33].…”
Section: Discussionmentioning
confidence: 60%
“…The reported mechanisms for the L-carnitine antiperoxidative role include inhibition of xanthine oxidase activity, scavenger action of free radicals, and chelation of the iron required for the generation of hydroxyl radicals [45,46] or by facilitating the fatty acids transport, thereby lowering the availability of lipids for peroxidation [47]. Reinforcing the hypothesis that L-carnitine could prevent lipid peroxidation in HMGA, this same protective effect was observed in other inborn errors of metabolism, such as in phenylketonuria [48], in maple syrup urine disease [24,31], and in disorders of propionate metabolism [28,33].…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have reported Se and Zn deficiencies in children and adolescents with PKU [15] but also normal plasma Se and Zn levels [21]. Reduced antioxidant capacity was described in subjects with PKU, and Se supplements were considered in the light of oxidative stress parameters [22]. Moreover, omega-3 docosahexaenoic acid (DHA) can play a role in alleviating oxidative stress and DHA supplementation has been shown to have health benefits in children with PKU [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our results in this study are also in agreement with the data reported by Mc Guire et al (2009), showing a marked reduction of urinary AOx in patients with PA. Interestingly, we found that patients under therapy also presented deficiency of their urinary AOx. It is presumed that these alterations can occur because of the treatment with restricted diets (such as in phenylketonuric patients) which are poor in micronutrients necessary for the antioxidant status or, alternatively, by an unusual increase in metabolic by-products which will directly or indirectly deplete the cell's antioxidant capacity (Moyano et al 1997;Wajner et al 2004;Sitta et al 2011;Ribas et al 2011).…”
Section: Discussionmentioning
confidence: 99%